(untitled) - Price, Brad (San Francisco, 2004)
Advanced Coverage for Experienced Network Administrators Active Directory Best Practices 24seven is written specifically to build on the practical and conceptual knowledge you've already earned. Taking a "just the facts, ma'am" approach this book provides targeted instruction and insider tips to help you quickly implement the best practices established by successful network administrators across a wide range of industries. This is also an excellent way to make a pain-free transition to the latest release of Active Directory.
Keywords: Directory services (Computer network technology),Thư mục dịch vụ (Mạng máy tính công nghệ),Microsoft Windows (Computer file),Microsoft Windows (Tập tin máy tính)